Experimental investigation of the use of sharp edges for the production of positive ions in field-ionization mass spectrometry - Blenkinsop, P.A.; Job, B.E.; Brailsford, David F.; Cross, C.M.; Robertson, A.J.B. (Elsevier, 1968)
Various commercial razor blades have been tested for field ionization performance and compared with edges prepared electrochemically from platinum and tungsten foils. The results are correlated with data obtained from electron micrographs of the various edges. It is concluded that tungsten edges offer the best compromise between field ionization efficiency and durability of the edge.